Effect of hand removal and organic spray on maturity, yield, quality and economics of banana (Musa paradisiaca) cv. Grand Naine - G R, NITHYA; TANDEL, B M; BHATT, S T; S, CHANDANA (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during 2021–22 at Navsari Agricultural University, Navsari, Gujarat, to investigate the effect of hand removal and organic sprays on banana maturity, yield and quality to improve productivity and income for growers. The experiment was laid out using a factorial completely randomised design (F-CRD) with three levels of lower hand removal and seven types of organic sprays, forming twenty-one treatment combinations with three replications in banana (Musa paradisiaca). After full bunch emergence, distal hands along with the male bud were removed, followed by sprays at 15 and 30 days after bunch emergence. The results revealed that removal of three hands (H3) significantly promoted early maturity (82.10 days), highest third-hand weight (3.08 kg), finger length (24.45 cm), finger girth (11.00 cm), TSS (18.51°Brix), reducing sugar (6.62%) and total sugar (14.58%). In contrast, removal of one hand (H1) recorded the greatest bunch weight (33.64 kg), bunch length (94.18 cm) and yield (116.80 t/ha). Among organic sprays, 5% Gliricidia leaf extract (O5) recorded early maturity (80.22 days), maximum bunch weight (37.50 kg), bunch girth (116.28 cm), third-hand weight (3.40 kg), finger length (24.63 cm), finger girth (11.42 cm), yield (130.20 t/ha), reducing sugar (6.84%) and total sugar (14.93%). In interaction, removal of three hands and Gliricidia leaf extract 5% (H3O5) showed early maturity (76.67 days), maximum third-hand weight (3.50 kg) and finger length (26.03 cm). Whereas, removal of one hand and Gliricidia leaf extract 5% (H1O5) gave maximum bunch weight (43.63 kg), yield (151.49 t/ha), net return (₹16,13,170/ha) and BCR (4.53). Thus, removal of one hand and spray of Gliricidia leaf extract 5% at 15 and 30 days gave the highest yield and net return in banana.